The Influence Of Motivation On The Development Of Students’ Personal And Professional Qualities - Tanirbergenovna Mamekova, Assem; Tanirbergenovna Naubayeva, Khapiza; K. Kerimbayeva, Rysty; Nursaitovna Galiyeva, Aigul; Shugayevna Akhmetova, Tulesh; Muratovna Issabayeva, Zauresh (Opción, 2019)
The paper deals with the problem of the development of personal and pro- fessional qualities in psychology students, as well as the formation of mo- tivation. The authors review works of famous psychologists involved in the study of motivation. They study the plurality of understanding of the essence of motivation, as well as the nature, structure, and functions of mo- tives. The paper considers a variety of factors influencing the formation of students’ motivation for their studies. The authors conclude that the level of the development of a student’s motivational sphere depends on the methods, conditions, and means of training, the awareness of the meaning of studying for the person involved, the subject and reflexive attitude to studying, as well as the subjective activity and subjective attitude.